Lessons Learnt from Library Sessions and Implication on Teaching of Information Literacy Skills in Higher Education: A Commentary (British Journal of Multidisciplinary and Advanced Studies, 2024)
Information literacy skills in higher education is an important skill needed by all students as demands for literacy skills keep getting higher.  The description of what used to be literate keeps changing as technology keeps unfolding and putting demands on academic librarians and their ability to provide literacy that can stand the test of time. Students from varying environment with digital divide still abound and coupled with lack of basic information literacy skills struggle in their academic engagements.  Academic librarians inundated with varying questions around lack of information skills must be proactive and think outside the box if they are to provide academic solutions. Librarians are now required to consistently improve their knowledge and be more resourceful if they are to provide aids to students’ information gaps and lack of literacy skills.  This paper is a commentary that uses Dervin sense making as a guide.